Fibroadenoma of the breast with florid epithelial cells hyperplasia: a case report - Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Fibroadenoma is a benign biphasic tumor of the breast, composed of an epithelial and a stroma component. Fibroadenoma with epithelial cells hyperplasia may contribute to the higher risk of breast cancer, especially for florid and atypical hyperplasia. The distinction between fibroadenoma with florid epithelial cells hyperplasia, in-situ carcinoma and invasive duct carcinoma of the breast ban be difficult morphologically. To solve the problem, immunohistochemical staining with specific andibodies will be helpfull in distinguishing usual duct hyperplasia from ductal carcinoma in situ. A case of fibroadenoma with florid epithelial cells hyperplasia has been reported. Morphologically, this tumor is difficult to be differentiated from ductal carcinoma. Immunohistochemical staining with High molecular weight cytokeratins 34BE12, Smooth Muscle Actin (SMA),E-cadherin could be used to determine the diagnosis of this tumor.